Effect of Meperidine on Equine Blood Histamine, Tryptase, and Immunoglobulin-E Concentrations - Trenholme, H. Nicole; Sakai, Daniel M.; Berghaus, Londa J.; Hanafi, Amanda L.; Knych, Heather K.; Ryan, Clare A.; McHale, Brittany; Banovic, Frane; Quandt, Jane E.; Barletta, Michele; Reed, Rachel A. (Frontiers in Veterinary Science, 2020)
Objectives: To evaluate changes in immunological parameters following subcutaneous (SC) and intramuscular (IM) administration of meperidine in horses through quantitative analysis of plasma tryptase, histamine, and IgE levels. Methods: Six adult horses were enrolled in a prospective randomized crossover design. Horses were administered one treatment per day, with a seven day washout period: a) meperidine 1 mg/kg IM, saline 6 mL SC; b) saline 6 mL IM, meperidine 1 mg/kg SC; c) saline 6 mL SC, saline 6 mL IM. Blood samples were obtained for plasmatic histamine (baseline, 5, 10, 15, 30, and 60 minutes) via LC-MS/MS and plasmatic tryptase (baseline, 15, 30, 60, 120, and 240 minutes) quantification with enzyme-linked immunoabsorbent assays. Serum immunoglobulin E (IgE) concentrations prior to any meperidine treatment and 7-14 days following the first meperidine treatment were evaluated with enzyme-linked immunoabsorbent assays. Histamine and tryptase concentrations were evaluated with a mixed-effect analysis of variance. The levels of IgE at baseline (before the administration of the first dose of meperidine) were compared with the IgE values at 60 minutes following the second meperidine administration with the Paired t test. Biopsies of localized injection site reactions from subcutaneous meperidine administration were collected from two horses. Results: No statistically significant elevations from baseline in histamine (p = 0.595), tryptase (p = 0.836) or IgE (p = 0.844) were found in any of the horses in this study. There were no differences between treatment groups. Administration of SC meperidine caused a localized vasculitis and thrombosis with regional edema and hemorrhage. Conclusion: No evidence of anaphylactoid or anaphylactic type reactions occurred following IM or SC meperidine administration.